OWN / ALIEN CHRONOTOPE AS A MARKER OF CHARACTER’S IDENTITY IN THE NOVELS BY MYROSLAV DOCHYNETS - Ищенко, Елена (Літературний процес: методологія, імена, тенденції, 2018)
The article is devoted to the study of Own / Alien chronotope as a marker of protagonist’s identity in the novels by modern Ukrainian writer M. Dochynets. It is revealed that his prose pays special attention to the relationship between the person and the environment, emphasizing the priority value of the chronotopic coordinates in shaping the attitude of the characters, their way of thinking, moral and ethical rules of conduct, the original philosophy, etc. The author repeatedly focuses on the relationship between the characters and the environment, using time-spatial parameters as a means of typing and individualization. The writer manifests this idea, using chronotropic characteristics for the naming of the characters Centenarian, Svitovan, Strider of the World, Highlander, The Digger of wells, Greek, etc., which emphasizes their interrelation with the natural environment. The parameters of Own / Alien chronotope influence on the identity of the characters in the dimensions: individual, social and national. Memories of the past complement the storyline and help to trace the process of self-identification of characters, explain their identity, help determine the factors that have influenced the formation of ecological consciousness and formed the rules of ecocultural behavior. The protagonists of the writer are people of respectable age who are presented at the beginning of the writings as psychologically formed individuals with rich life experiences: numerous travels (going beyond their Own space and interacting with Alien), meeting with different people, physical and psychological tests, etc. M. Dochynets depicts the process of forming identities (individual, social, national) as a harmonious component of selfknowledge and spiritual self-improvement of protagonists in novels “Centenarian. Confession on the Pass of the Spirit”, “Svitovan. Studies under the Celestial Dome”, “The Digger of Wells. The Diary of the Richest Man of the Mukachevo Dominion”, “Highlander: Waters of Our Lord’s Riverbeds”, “Maftay. A book Written with a Dry Pen”. The identity of the individual identification of heroes is to identify itself as an organic part of the Universe.